Eosinophilic esophagitis: which role for food and inhalant allergens? - Ridolo, Erminia (Asia Pacific Association of Allergy, Asthma and Clinical Immunology, 2012)
Eosinophilic esophagitis is a chronic inflammatory disease of the esophagus, immune/antigens mediated, whose incidence is increasing both in adults and pediatric population. It is clinically characterised by symptoms related to esophageal dysfunction and associated with eosinophil-predominant esophageal inflammation. The role of atopy has been clearly demonstrated both in epidemiological and experimental studies and has important implications for diagnosis and therapy. In fact, many evidences show that food and inhalant allergens represent the most important factors involved in the progress of the disease. Several studies have reported that, in a range between 50 and 80%, patients with eosinophilic esophagitis have a prior history of atopy, and for them, the presence of allergic rhinitis, asthma or atopic dermatitis is frequent. Skin tests are able to identify in most patients the allergens involved, allowing a correct dietary approach in order to achieve the remission of symptoms and the biopsy normalization.